2021
DOI: 10.5455/msm.2021.33.70-74
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia, Stress and Depression in Infertile Women: a Case Control Study

Abstract: Background: Alexithymia and stress are two main psychological factors which affect not only fertility, but also the outcome of assisted reproductive technology treatment. Objective: The primary aim of this study was to compare the levels of alexithymia and stress between infertile women undergoing assisted reproductive treatment and women with no fertility issues. The present study aims to: (i) explore the relation between alexithymia and infertility, (ii) investigate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This trend suggests a greater reliance on a concrete cognitive approach, possibly as a defense mechanism against the challenges of a difficult and overwhelming experience. This finding aligns with a recent study that reported similar levels of alexithymia among women facing infertility problems, compared to women without fertility problems [60], although it is not consistent with previous infertility studies [41,43,61].…”
Section: Discussionsupporting
confidence: 63%
“…This trend suggests a greater reliance on a concrete cognitive approach, possibly as a defense mechanism against the challenges of a difficult and overwhelming experience. This finding aligns with a recent study that reported similar levels of alexithymia among women facing infertility problems, compared to women without fertility problems [60], although it is not consistent with previous infertility studies [41,43,61].…”
Section: Discussionsupporting
confidence: 63%
“…Our results were compatible with some studies that have shown an association between alexithymia and a number of psychological problems. 4,18,19 In an explorative study it is revealed that higher maternal alexithymic traits associate with lower maternal sensitivity and more hostile maternal caregiving behavior. 3 According to another trial, maternal fetal relationship was negatively associated with maternal anxiety and alexithymia and was positively associated with social support.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between psychological factors (stress, anxiety, and depression) and infertility is rather complex, multifactorial, and bidirectional [ 17 ]. Thus, the present study aims to capture the prevalence of stress, depression, and anxiety among infertile and fertile women and to understand the relationship of psychological variables with each other.…”
Section: Introductionmentioning
confidence: 99%